Application of comprehensive prediction method of water inrush hazards induced by unfavourable geological body in high risk karst tunnel: a case study. Issue 2 (15th December 2017) - Shi, Shaoshuai; Bu, Lin; Li, Shucai; Xiong, Ziming; Xie, Xiaokun; Li, Liping; Zhou, Zongqing; Xu, Zhenhao; Ma, Dan
ABSTRACT: While tunnelling in karst terrains, karst fissure water may endanger the safety of tunnel engineering and cause geological disasters such as water inrush. To ensure the safety of tunnel construction, in investigation stage, engineering geological and hydrogeological conditions of Jigongling Tunnel was analysed firstly. In design stage, a reasonable prediction method combining with optimization principle was selected to calculate the water inflow according to the geological and hydrogeological conditions analysed in the investigation stage. Then the advanced geological prediction was divided into different classes based on the water inflow. To make an accurate prediction, tunnel seismic prediction method, transient electromagnetic method, induced polarization method and advanced geological drilling were comprehensively applied in construction stage. This method combined with geology analysis, water inflow calculation and classification of advanced geological prediction is successfully applied in the Jigongling Tunnel of Fanba Expressway, and has provided a reference for the similar engineering constructions.